User innovation barriers and their impact on user-developed products - Thorsten Pieper; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2018)
User innovation is a broadly discussed phenomenon in the context of open innovation which describes, for instance, the customer integration into the early phases of new product development). Despite there existing a large body of research in the field of lead users and user innovation, scientific literature provides only a few insights into how barriers are influencing user innovators and their development processes (Braun and Herstatt, 2007). In addition, there is still little research into the effects of user innovation barriers on user-generated products, and how user innovators' personal characteristics remedy or foster the effect of barriers on user-generated products along the user innovation process. Accordingly, this study contributes to lead user and user innovation theory by analyzing quantitative data from 299 respondents in the field of Fab Labs and makerspaces. An empirical model comprising user innovation barriers (technological, social, legal and ownership), user innovators' personal traits (lead userness and openness) and user innovations' product properties (perceived complexity) is analyzed by applying multivariate regression methods. Findings from the study reveal a hierarchical allocation of the barriers' impacts on the dependent variable perceived complexity, along the development stages. Barriers in user innovation processes serve as factors hindering, but also promoting, user innovation activities. It has been found, for instance, that technological barriers in the conceptualization and social barriers in the prototyping phase increase user innovations' perceived complexity. Instead, legal barriers in prototyping even decrease perceived complexity. Furthermore, an influence of openness as a direct and moderating personal trait to overcome user innovation barriers has been confirmed by this study.
Keywords: 330; Open and User Innovation; User Innovation Process; User Innovator Characteristics; Lead User Research; Collaborative Workspaces